Effects of Hericium erinaceus Mycelium Extracts on the Functional Activity of Purinoceptors and Neuropathic Pain in Mice with L5 Spinal Nerve Ligation. (14th May 2020) - Yang, Pao-Pao; Chueh, Sheau-Huei; Shie, Hua-Lun; Chen, Chin-Chu; Lee, Li-Ya; Chen, Wan-Ping; Chen, Yu-Wen; Shiu, Li-yen; Liu, Pei-Shan
Abstract : Neuropathic pain is a serious clinical problem that is difficult to treat. Purinoceptors (P2Rs) transduce pain perception from the peripheral to the central nervous system and play an important role in the transmission of neuropathic pain signals. We previously found that the crude extracts of Hericium erinaceus mycelium (HE-CE) inhibited P2R-mediated signaling in cells and reduced heat-induced pain in mice. The present study explored the effects of HE-CE on neuropathic pain. We used adenosine triphosphate (ATP) as a P2R agonist to generate Ca 2+ signaling and neuronal damage in a cell line. We also established a neuropathic mouse model of L5 spinal nerve ligation (L5-SNL) to examine neuropathic pain and neuroinflammation. Neuropathic pain was recorded using the von Frey test. Neuroinflammation was evaluated based on immunohistofluorescence observation of glial fibrillary acidic protein (GFAP) levels in astrocytes, ionized calcium-binding adaptor molecule1 (iba1) levels in microglia, and IL-6 levels in plasma. The results show that HE-CE and erinacine-S, but not erinacine-A, totally counteracted Ca 2+ signaling and cytotoxic effects upon P2R stimulation by ATP in human osteosarcoma HOS cells and human neuroblastoma SH-SY5Y cells, respectively. SNL induced a decrease in the withdrawal pressure of the ipsilateral hind paw, indicating neuropathic pain. It also raised the GFAP level in astrocytes, the iba1 level in microglia, and the IL-6 level in plasma, indicating neuroinflammation. HE-CE significantly counteracted the SNL-induced decrease in withdrawal pressure, illustrating that it could relieve neuropathic pain. It also reduced SNL-induced increases in astrocyte GFAP levels, microglial iba1 levels, and plasma IL-6 levels, suggesting that HE-CE reduces neuroinflammation. Erinacine-S relieved neuropathic pain better than HE-CE. The present study demonstrated that HE inhibits P2R and, thus, that it can relieve neuropathic pain and neuroinflammation.